Amerique Septentrionale - Laguillermie; Bonheur, Raimond; Levasseur, V.
This map shows North and Central America and the surrounding areas. Countries are outlined and shaded in various colors. Some major cities, bodies of water, and geographic features are marked (with relief shown by hachures). Around the outside of the maps, there are various colored illustrations showing people, landscape, and animals. At the bottom of the page, there are two blocks of text; the the right, statistics regarding population, and to the right, "Explication du dessin."